Methods of Administrative and Legal Protection of Tax Relations: Theoretical and Legal Study (Law and Safety, 2019)
The author of the article has provided the results of the analysis of the methods of administrative and legal protection taking into account the changes within the relations between public administration and taxpayers and the course chosen by the state for liberalization of tax relations.The place of the concept of the methods of administrative and legal protection in the term system of the science of administrative law and their dialectical relations with the methods of public administration and administrative activity has been established.The author has indicated generic and specific features of the methods of administrative and legal protection of tax relations, where the latter will depend on the peculiarities of the means and methods of influence used by the public administration for the purpose of exercising security functions.The system of methods of administrative and legal protection of tax relations has been offered to form from three elements: general methods of administrative activity (persuasion and coercion), service tools of influence (provision of administrative services, creation of electronic services and publication of open data sets) and organizational methods. The expediency of distinguishing service means of influence into a separate group of methods of administrative and legal protection has been proved. It is conditioned by their special functional purpose – creation of conditions for independent prevention of possible breach of protected relations by the taxpayer. The role and correlation of persuasion and coercion in the system of methods of administrative and legal protection of tax relations have been clarified. Despite the presented importance of the persuasion within the relationship between the controlling agencies and the taxpayers, it has been stated that state coercion remains the main mean of administrative and legal protection of tax relations.Particular attention has been paid on the need to reconsider the correlation of tax and administrative coercion within tax relations. It has been proved that the basis of their delimitation should be not the branch of legislation, where the authority to apply the appropriate measure is assigned, but the essential criterion and the subject matter of regulation (influence) – relations arising from incomplete calculation and late and incomplete payment of taxes and fees, or relationships related to the organization and enforcement of tax responsibilities and the proper exercise by the supervisory authorities of their powers. It has been emphasized that tax coercion, unlike administrative, performs both punitive and compensatory functions.
Keywords: administrative and legal protection; tax relations; methods; persuasion; coercion